The Role of International Trade in Increasing The Rate of Economic Growth in Indonesia: A Literature Review - Matondang, Khairani Alawiyah; Silalahi, Hanna Hotmian Br; Naibaho, Hotmaria Silva Dewi; Safitri, Laila; Siregar, Abed Nego (LPPPIPublishing, 2024)
In the increasingly fast current of world globalization, there are currently no restrictions between one country and another. Cooperation and alliances can be established in all corners of the world, one of which is through international trade activities. This research aims to find out what the actual correlation is between international trade and the pace of the economy in Indonesia. The research method used in this research is literature study. Studies from substantial sources confirm that international trade is closely related to economic growth. Through international trade activities, it helps a country to minimize resource, technological and market constraints. In essence, international trade is a connecting point for the countries concerned to increase productivity and efficiency for economic sustainability in their countries.